Load Bearing Type Car Body of DAS7 Overhead Catenary System Comprehensive Maintenance Vehicle - REN Tao-long; ZHAO Guo-dong; ZHANG Ling-hong (机车电传动)
Design, calculated work status and evaluation criteria of load bearing car body of DAS7 overhead catenary system comprehensive maintenance vehicle were introduced, as well as car-body structure and summarized structural & weight optimization design. Strength test showed that through light-weight design, quality of the vehicle was reduced, but structural strength enhanced.